Establishment of Dental Pulp Cell Culture System for Analyzing Dentinogenesis in Mouse Incisors - Yuka Kato; Insoon Chang; Satoshi Yokose (Dentistry Journal)
Background: The dentin–pulp complex plays a vital role in tooth health. Dentin forms the main body the tooth and continues to form throughout life to maintain homeostasis and provide protection against deleterious external stimuli. However, the detailed mechanism of dentin formation remains poorly understood, and there is a need for new regenerative therapies. This study therefore investigated whether primary dental pulp cells from mice could be used to establish a new culture system. Methods: Mouse mandibles were divided along the ramus to extract dental pulp tissue containing cervical loops. The extracted tissue was cultured in an incubator to promote cell out-growth and increase the number of cells available for experimentation. Results: Cultured cells formed mineralized nodules, confirmed by Alizarin red S staining. The expression levels of dentin sialo protein, bone gamma-carboxyglutamate protein, and type I collagen mRNAs in cultured dental pulp cells on day 15 were lower than those in intact mouse dental pulp tissue, and the expression of all mRNAs was confirmed through electrophoresis. Conclusions: This study established a primary culture system using dental pulp tissue extracted from mouse mandibular incisors. The results demonstrated that dental pulp cells can differentiate into odontoblast-like cells and form dentin-like mineralized nodules, thereby offering a useful system for studying dentin formation and odontoblast differentiation.